2011
DOI: 10.1126/science.1192149
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical TGFβ Signaling Contributes to Aortic Aneurysm Progression in Marfan Syndrome Mice

Abstract: Transforming growth factor–β (TGFβ) signaling drives aneurysm progression in multiple disorders, including Marfan syndrome (MFS), and therapies that inhibit this signaling cascade are in clinical trials. TGFβ can stimulate multiple intracellular signaling pathways, but it is unclear which of these pathways drives aortic disease and, when inhibited, which result in disease amelioration. Here we show that extracellular signal–regulated kinase (ERK) 1 and 2 and Smad2 are activated in a mouse model of MFS, and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
459
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 428 publications
(487 citation statements)
references
References 27 publications
22
459
4
2
Order By: Relevance
“…TGFb, a central molecule in the pathogenesis of Marfan aortopathy 12,14,[32][33][34] , and its downstream signalling pathways (canonical pSmad2 (ref. 35) and non-canonical pERK1/2 (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFb, a central molecule in the pathogenesis of Marfan aortopathy 12,14,[32][33][34] , and its downstream signalling pathways (canonical pSmad2 (ref. 35) and non-canonical pERK1/2 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advancements in understanding mechanisms of aortic disease have stemmed from hallmark studies in the genetically fragile Marfan aorta, which have shown that transforming growth factor b (TGFb) and its downstream intracellular kinase signalling pathways play a central role in the pathogenesis [12][13][14] . In contrast, an inflammatory pathway is thought to be a major component of aortic conditions in the atherosclerotic/ degenerative aorta seen in the typical elderly patient 15,16 .…”
mentioning
confidence: 99%
“…1,2 During the last decade, it has become increasingly clear that dysregulated transforming growth factor beta (TGFb) signaling is having a major role in the pathogenesis of MFS, LDS, and related disorders involving thoracic aortic aneurysms. [3][4][5][6][7][8][9] Because of the overlap with MFS and LDS and because several lines of evidence have confirmed a key role of TGFb signaling in the pathogenesis of MFS and LDS, it was hypothesized that altered TGFb signaling also underlies the SGS pathogenesis. Indeed, de novo, heterozygous mutations in SKI (Sloan-Kettering Institute), encoding a known repressor of TGFb signaling, were identified in 10 SGS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with Down, Marfan, or Noonan Syndromes, there is increasing evidence that genes encoding nodal signaling kinases like FAK/AKTkt/PI3K, RAS, MEKK/ ERK1/2, PTPN11, etc., are likely candidates for CHD if they are mutated or overexpressed [2][3][4]. Such genes are not usually lethal (as there exist molecular or functional redundancies), yet as indicated for syndromic heart defects, they have potential to change functional behaviors in progenitor cells that normally mold and remodel the simple tubular heart into a four-chambered organ.…”
Section: Nodal Signaling Kinasesmentioning
confidence: 99%
“…The evolution of genetic thought is toward trans-heterozygous, multigenetic interactions vs. single gene hits. 3. Mutations in the downstream intracellular signaling targets of growth factor, transcription factors, or matricellular proteins are more likely to be the root cause of heart defects seen in children by pediatric cardiologists (as the loss of both alleles for upstream early regulatory genes is usually lethal).…”
Section: Emerging Conceptsmentioning
confidence: 99%